Bacterial tRNA 2′-O-methylation is dynamically regulated under stress conditions and modulates innate immune response. Issue 22 (4th December 2020) - Galvanin, Adeline; Vogt, Lea-Marie; Grober, Antonia; Freund, Isabel; Ayadi, Lilia; Bourguignon-Igel, Valerie; Bessler, Larissa; Jacob, Dominik; Eigenbrod, Tatjana; Marchand, Virginie; Dalpke, Alexander; Helm, Mark; et al.
Abstract: RNA modifications are a well-recognized way of gene expression regulation at the post-transcriptional level. Despite the importance of this level of regulation, current knowledge on modulation of tRNA modification status in response to stress conditions is far from being complete. While it is widely accepted that tRNA modifications are rather dynamic, such variations are mostly assessed in terms of total tRNA, with only a few instances where changes could be traced to single isoacceptor species. Using Escherichia coli as a model system, we explored stress-induced modulation of 2′-O-methylations in tRNAs by RiboMethSeq. This analysis and orthogonal analytical measurements by LC-MS show substantial, but not uniform, increase of the Gm18 level in selected tRNAs under mild bacteriostatic antibiotic stress, while other Nm modifications remain relatively constant. The absence of Gm18 modification in tRNAs leads to moderate alterations in E. coli mRNA transcriptome, but does not affect polysomal association of mRNAs. Interestingly, the subset of motility/chemiotaxis genes is significantly overexpressed in ΔTrmH mutant, this corroborates with increased swarming motility of the mutant strain. The stress-induced increase of tRNA Gm18 level, in turn, reduced immunostimulation properties of bacterial tRNAs, which is concordant with the previous observation that Gm18 is a suppressor of Toll-like receptor 7 (TLR7)-mediated interferon release. This documents an effect of stress induced modulation of tRNA modification that acts outside protein translation.